Concepts for dynamic barrier management. (September 2016) - Pitblado, R.; Fisher, M.; Nelson, B.; Fløtaker, H.; Molazemi, K.; Stokke, A.
Abstract: Safety barrier management is an important activity to maintain or reduce process safety risk of an operating facility. Barriers can be hardware, human or organizational, or some combination of these. Barriers are normally fully functional after installation or commissioning when all equipment has been tested and all staff trained, and the facility risk will be at or better than target level, as the design risk assessment this will have assumed some barrier failure probability. However, barriers degrade at different rates, and these degradations start to increase facility risk. Some barrier failures can increase risk dramatically, especially where barrier dependencies exists. Conventional barrier management applies fixed inspection and maintenance intervals to these with the intent to return these to full functionality and the risk to target, but take no account of dependencies. Dynamic barrier management uses the full suite of information available, including direct and indirect indicators of barrier performance to infer barrier status in near real-time. This can be through a smart combination of inspection, preventive maintenance, audit, sensors, process control, and near-miss or incident records, and big data concepts. Barrier maintenance can then be planned optimally based on quantitative barrier importance to risk control, in a manner similar to risk based inspection (RBI). Higher Importance barriers (i.e. risk affecting) would be assigned higher priority than other barriers. This can achieve better safety at lower cost than current barrier management processes. This paper presents the concepts for dynamic barrier management. All the details have been developed and this completes the design phase activity. A practical application will be next to prove these ideas. Highlights: Safety barriers are now growing as a key means to manage operational safety. Barriers are of multiple types and degrade at different rates. Multiple data sources are used to determine near-real time barrier status. Each barrier is assessed for risk importance. Dynamic barrier management uses repairs barriers achieving better safety at lower cost.